CRIMINOLOGICAL APPROACH OF GENDER AND INTRAFAMILY VIOLENCE IS THE CRIMINAL RESPONSE EFFECTIVE? - Ríos Patio, Gino (2019)
The author exposes, from a criminological perspective, the causes of gender and intrafamily violence and analyzes whether the criminal response is effective in preventing and reducing this type of violence. It proposes criminological policy guidelines to face the increase of these aggressive behaviors that erode the family nucleus and therefore the social base.